A unique opportunity to study short and long term consequences in children prenatally exposed to illicit drugs and opioid maintenance treatment using Czech and Scandinavian registers - Gabrhelík, Roman; Nechanská, Blanka; Mravčík, Viktor; Skurtveit, Svetlana; Lund, Ingunn Olea; Handal, Marte (Central European Journal of Public Health, 2016)
Licit and illicit drug use in pregnant women constitutes a long lasting and serious problem worldwide. Information on long-term effects of maternal drug use on the child is limited. Nationwide registers provide a great potential to study short and long-term consequences for children exposed to licit and illicit drugs during pregnancy. We discuss this potential, with a special emphasis on exposure to methamphetamine, heroin and prescription drugs used for opioid maintenance treatment (OMT). We also discuss the advantages of register data and of merging such data from different regions. The Czech and Scandinavian registers are largely comparable and provide great opportunities to conduct innovative research. For instance, using Czech and Scandinavian cohorts we can compare groups with similar characteristics, such as mothers in OMT and mothers addicted to other drugs while also controlling for important confounding factors such as health and socio-economic status.
Keywords: methamfetamin; dospělí; Opiate Substitution Treatment; heroin; Female; narkotika - antagonisté; Methamphetamine; Illicit Drugs; Analgesics, Opioid; zakázané drogy; novorozenec; Adult; ženské pohlaví; Registries; Scandinavian and Nordic Countries; Narcotic Antagonists; lidé; Heroin; Infant, Newborn; Pregnancy Outcome; těhotenství; zpožděný efekt prenatální expozice; opioidní analgetika; Czech Republic; Prenatal Exposure Delayed Effects; výsledek těhotenství; Skandinávie a severské státy; Česká republika; Substance-Related Disorders; lidé středního věku; registrace; poruchy spojené s užíváním psychoaktivních látek; Pregnancy; opiátová substituční terapie; Middle Aged; Humans